Results of an international survey on the use and perceptions of the laryngeal mask airway (LMA) - Natalie Krug; Volker Thieme; Maria Theresa Voelker; Sven Bercker (PLoS ONE, 2025)
Background and objectives Laryngeal Mask Airway (LMA) are valuable tools for airway management in anaesthesia and offer advantages in various scenarios. However, due to a lack of data, for many aspects of its application no standards and clear limitations are used. Methods Between May 15th and June 15th 2023, a link to an online-based survey was sent via email to members of the European Society of Anaesthesiology and Intensive Care (ESAIC). The survey included 16 questions on attitudes regarding weight limit, patient positioning, positive end-expiratory pressure (PEEP) and peak inspiratory pressure (PIP) limits, surgical procedures, their duration and ventilation modes when using LMA as well as level of experience and nationality. Results The survey was sent to 7145 recipients, 345 of whom completed the survey. The respondents came from 54 countries, including 31 from European countries. 121 anaesthetists (31.9%) reported considering an upper limit of Body-Mass-Index (BMI) when using a LMA (median 35 kg/m²), 186 (49.1%) reported a maximum duration of use (median 120 minutes), 223 anaesthetists (58.8%) reported a PEEP limit (median 5 mBar) and 238 (62.8%) a PIP limit (median 22,5 mBar). 179 (47.2%) use LMA only in supine position, 53 (14%) in supine and prone position and 147 (38.8%) in supine, side and prone position. The majority (n=322; 85%) do not use LMA for procedures with increased intra-abdominal pressure such as laparoscopy. Conclusion The results of this survey demonstrate very heterogeneous practices and perceptions of ESAIC anaesthetists regarding the use of LMA in different circumstances. Our data suggest that there is no consistent or widely accepted strategy on these issues. Anaesthetists should have a strong interest in resolving these uncertainties by conducting international randomised prospective trials.